Medicinal [Delta]9-tetrahydrocannabinol (dronabinol) impairs on-the-road driving performance of occasional and heavy cannabis users but is not detected in Standard Field Sobriety Tests - Bosker, Wendy M.; Skopp, Gisela (Addiction, 2012)
Aims The acute and chronic effects of dronabinol [medicinal Δ9-tetrahydrocannabinol (THC)] on actual driving performance and the Standard Field Sobriety Test (SFST) were assessed. It was hypothesized that occasional users would be impaired on these tests and that heavy users would show less impairment due to tolerance. Design, setting and participants Double-blind, placebo-controlled, randomized, three-way cross-over study. Twelve occasional and 12 heavy cannabis users (14 males/10 females) received single doses of placebo, 10 and 20 mg dronabinol. Measurements Standard deviation of lateral position (SDLP; i.e. weaving) is the primary measure of road-tracking control. Time to speed adaptation (TSA) is the primary reaction-time measure in the car-following test. Percentage of impaired individuals on the SFST and subjective high on a visual analogue scale were secondary measures. Findings Superiority tests showed that SDLP (P = 0.008) and TSA (P = 0.011) increased after dronabinol in occasional users. Equivalence tests demonstrated that dronabinol-induced increments in SDLP were bigger than impairment associated with BAC of 0.5 mg/ml in occasional and heavy users, although the magnitude of driving impairment was generally less in heavy users. The SFST did not discriminate between conditions. Levels of subjective high were comparable in occasional and heavy users. Conclusions Dronabinol (medicinal tetrahydrocannabinol) impairs driving performance in occasional and heavy users in a dose-dependent way, but to a lesser degree in heavy users due possibly to tolerance. The Standard Field Sobriety Test is not sensitive to clinically relevant driving impairment caused by oral tetrahydrocannabinol.